How Does Financial Reporting Regulation Affect Firms’ Banking? - Breuer, Matthias; Hombach, Katharina; Müller, Maximilian A (Review of Financial Studies, 2018)
We examine the effects of financial reporting regulation on firms’ banking. Exploiting discontinuous public disclosure and auditing requirements assigned to otherwise similar small and medium-sized private firms, we document that financial reporting regulation reduces firms’ reliance on concentrated and local bank relationships and increases banks’ reliance on firms’ financial reporting, consistent with a shift in firms’ banking from relationship toward transactional approaches. Our evidence suggests that financial reporting regulation substitutes for banks’ information production role by burdening firms with the disclosure and auditing of their financial statements, consistent with institutional complementarities between reporting and banking systems. Received October 21, 2016; editorial decision September 15, 2017 by Editor Philip Strahan. Authors have furnished an Internet Appendix, which is available on the Oxford University PressWeb site next to the link to the final published paper online.